MANAJEMEN PELAJARAN BERBASIS KEARIFAN LOKAL MANDAR DALAM INTERNALISASI NILAI ISLAM MELALUI PROGRAM MBKM DI MTsN 1 MAJENE - Nurkhalisah M; Adliyah; Kamus; Emha Dzia’ul Haq; Armayanti; Hasnita; Surianto; Nurauliah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this article is to demonstrate how Islamic values are integrated into the local wisdom of the Mandar community through the teaching of Fiqh, the Qur’an, and Hadith in the Merdeka Belajar Kampus Merdeka (MBKM) program held at MTsN 1 Majene. This study explores the firsthand experiences of MBKM students as agents of learning in the field using a descriptive qualitative approach that employs participatory observation and daily reflective journals. The learning process is carried out through the Contextual Teaching and Learning (CTL) approach, which connects instructional material to students’ social and cultural experiences. The study’s findings indicate that sipattau (mutual humanity), sipakaraya (mutual respect), and sipaingarang (mutual reminders) are values of local wisdom that can be integrated into Fiqh and Qur’an-Hadith curricula, holding the potential to enhance students’ contextual and meaningful internalization of these values. Conversely, the active involvement of MBKM students in religious and extracurricular activities at the madrasah demonstrates their role as agents of change who extend the instillation of Islamic values beyond the classroom and foster a broad Islamic character in students.